2020
DOI: 10.3390/jof7010003
|View full text |Cite
|
Sign up to set email alerts
|

Immune Sensing and Potential Immunotherapeutic Approaches to Control Chromoblastomycosis

Abstract: Chromoblastomycosis (CBM) is a neglected, chronic, and progressive subcutaneous mycosis caused by different species of fungi from the Herpotrichiellaceae family. CBM disease is usually associated with agricultural activities, and its infection is characterized by verrucous, erythematous papules, and atrophic lesions on the upper and lower limbs, leading to social stigma and impacts on patients’ welfare. The economic aspect of disease treatment is another relevant issue. There is no specific treatment for CBM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 125 publications
(166 reference statements)
0
4
0
5
Order By: Relevance
“…The innate immune response is very important in both chromoblastomycosis and leprosy [34][35][36]. In immunosenescence, dysfunction of innate immunity cells is observed, causing a decrease in phagocytosis, destruction of fungal elements and an increase in the immunomodulation produced by the etiological agents of leprosy, facilitating the progression of both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune response is very important in both chromoblastomycosis and leprosy [34][35][36]. In immunosenescence, dysfunction of innate immunity cells is observed, causing a decrease in phagocytosis, destruction of fungal elements and an increase in the immunomodulation produced by the etiological agents of leprosy, facilitating the progression of both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This species shows a cosmopolitan distribution and is found in fresh and sea water, including swim-ming pools and aquariums, and generally infects fish, amphibians, and reptiles; rarely, human infection is documented [74]. Disease begins after traumatic contact with animals infected with this bacteria, and immunosuppressed humans are particularly at risk [102].…”
Section: Diversity Of Etiologic Agents Of Cbmmentioning
confidence: 99%
“…A number of studies have demonstrated that F . monophora exhibits neurotropism or causes primary brain infection without skin damage [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%